Penguatan Moderasi Beragama Melalui Nilai-Nilai Pendidikan Islam Dalam Kearifan Lokal Sedekah Pedusunan - Elhefni Elhefni; Alihawanah; Ahmad Syarifuddin; Tutut Handayani; Nurlaeli; Amir Hamzah; Miftahul Husni; Agra Dwi Saputra; Ria Safitri; Dyah Putri Ayu Fadhilah (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
This service activity aims to strengthen attitudes of religious moderation through the values ​​of Islamic education contained in the local wisdom of alms from the villages of Embacang Kelekar village, Kelekar subdistrict, Muara Enim district. The method used is the training method of strengthening religious moderation through Islamic education values in the local wisdom of Sedekah Pedusunan. The people of Embacang Kelekar Village have their own reasons for implementing this local wisdom. These reasons include: 1) To refuse balak, keep away disease, ask for good fortune and be grateful for what was obtained during the previous year. 2) To strengthen the community's sense of family. 3) To bring distant families closer together. Village almsgiving is carried out with the aim of gathering again and giving each other, either in the form of money or energy to help carry out rural almsgiving. In rural alms there are Islamic educational values ​​contained in it, namely i'tiqodiyah values, khuluqiyah values, and amaliyah values. The value of i'tiqodiyah is the sense of faith of citizens when reciting dhikr and reciting Yasin. Khuluqiyah values ​​include helping, compassion, gratitude, courtesy, forgiveness, discipline, keeping promises, honesty and responsibility. Furthermore, the value of charity is charity to fellow citizens. Through these values, it can be strengthened that the Embacang community has implemented an attitude of religious moderation through the local wisdom of village alms. The results of this activity are that 80% of the community understands the attitude of religious moderation.